Money makeover : the secret to budgeting, saving and investing for financial success - Dubecki, Nina; Rowsthorn, Vanessa (Wrightbooks, 2010)
You don't have to earn megabucks or have a degree in economics to make the most of your money. With the help of Money Makeover , you'll discover how easy it is to take stock of your finances and create the life of your dreams, without having to give up red wine or wade through finance mumbo-jumbo!. Inside this book you'll find practical information (without the boring bits) and inspiring real-life stories that will empower you to create your own financial plan. You'll discover: simple strategies to work your way out of debt; fail-proof saving techniques; how to invest in shares, managed funds